2021
DOI: 10.1371/journal.ppat.1010039
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific quantification of circulating ebolavirus burden using VP40-derived peptide variants

Abstract: Six ebolavirus species are reported to date, including human pathogens Bundibugyo virus (BDBV), Ebola virus (EBOV), Sudan virus (SUDV), and Taï Forest virus (TAFV); non-human pathogen Reston virus (RESTV); and the plausible Bombali virus (BOMV). Since there are differences in the disease severity caused by different species, species identification and viral burden quantification are critical for treating infected patients timely and effectively. Here we developed an immunoprecipitation-coupled mass spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Inspired by our previous work on developing a rapid diagnostic test for Ebola infectious disease, [ 44 ] we tested the 4‐h sample preparation workflow in the multiplexed IP‐MS assay of EsxN and CFP‐10 peptide variants. We selected four representative MGIT samples infected with Mtb or M. kansasii or MAC, and shorten the time of trypsin digestion of MGIT samples from 16 to 1 h. It showed that the peptide variant targets were all identified correctly for their species origin (Figure S5–S10).…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by our previous work on developing a rapid diagnostic test for Ebola infectious disease, [ 44 ] we tested the 4‐h sample preparation workflow in the multiplexed IP‐MS assay of EsxN and CFP‐10 peptide variants. We selected four representative MGIT samples infected with Mtb or M. kansasii or MAC, and shorten the time of trypsin digestion of MGIT samples from 16 to 1 h. It showed that the peptide variant targets were all identified correctly for their species origin (Figure S5–S10).…”
Section: Resultsmentioning
confidence: 99%